Perancangan Aspek Medicolegal Visum Et Repertum Berbasis Elektronik sebagai Alat Bukti Guna Menunjang Penegakan Hukum - Dhiu, Yuliana Angelina; Syahidin, Yuda; Sari, Irda (Program Studi Teknik Informatika Universitas Pamulang, 2024)
Technological developments have provided significant support for employee performance in hospitals, onel of which is in the medical record installation, namely the making of a visum et repertum in the medicolegal aspect. In the research that has been conducted, researchers found several problems in the medical records installation, one of which is the delay in making VeR because it is not fully computerized because it still uses Microsoft Word, resulting in less effective services. Therefore, a system is needed. The research methods used include literature study, observation, and interviews with descriptive analysis. The system development method uses the agile software development method. The results of this system design are expected to reduce the workload of officers, produce accurate information, maximize services and improve the quality of services in the hospital.